Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = 2x - 5}[/tex]
[tex]\mathsf{y = 2x - 5}[/tex]
[tex]\mathsf{x = 2y - 5}[/tex]
[tex]\mathsf{2y = x + 5}[/tex]
[tex]\mathsf{y = \dfrac{x + 5}{2}}[/tex]
[tex]\mathsf{f^{-1}(x) = \dfrac{x + 5}{2}}[/tex]
[tex]\mathsf{f^{-1}(1) = \dfrac{1 + 5}{2} = \dfrac{6}{2} = 3}[/tex]
[tex]\boxed{\boxed{\mathsf{D(1;3)}}}\leftarrow\textsf{letra D}[/tex]
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = 2x - 5}[/tex]
[tex]\mathsf{y = 2x - 5}[/tex]
[tex]\mathsf{x = 2y - 5}[/tex]
[tex]\mathsf{2y = x + 5}[/tex]
[tex]\mathsf{y = \dfrac{x + 5}{2}}[/tex]
[tex]\mathsf{f^{-1}(x) = \dfrac{x + 5}{2}}[/tex]
[tex]\mathsf{f^{-1}(1) = \dfrac{1 + 5}{2} = \dfrac{6}{2} = 3}[/tex]
[tex]\boxed{\boxed{\mathsf{D(1;3)}}}\leftarrow\textsf{letra D}[/tex]